Conceptualizing state strength: moving beyond strong and weak states - Giraudy, Agustina (Revista de Ciencia Política, 2019)
The strength of states has long been regarded by the specialized literature as an important factor to guarantee the viability of different political and economic phenomena such as democratic consolidation, the rule of law, adequate provision of basic public goods, and economic growth. Despite the importance of state strength, only few scholarly works have systematically explored the definition and the constitutive dimensions of this concept. This article seeks to (a) refine the conceptualization of state strength, (b) increase awareness about the effects of different rules of aggregation for achieving differentiation among empirical cases (i.e., countries), and (c) provide conceptual tools to help analysts move beyond the classical dichotomy of strong states versus weak states.